RESEARCH OF THE ISSUE OF AESTHETIC EDUCATION BASED ON KARAKALPAK ETHNOCULTURE BY LOCAL SCHOLARS - Bekbosinov, Dinmuxammatdin Abillaevich (SCIENCE and SOCIETY, 2026)
This article analyzes the scientific foundations of aesthetic education based on Karakalpak ethnoculture as explored in the works of local scholars. The study highlights the educational potential of folk oral creativity, national art, traditions, and cultural heritage of the Karakalpak people in fostering aesthetic awareness and artistic thinking among the younger generation. The pedagogical significance of integrating ethnocultural values into the educational process is substantiated, and the close relationship between aesthetic education and state spiritual and educational policies is emphasized. The findings confirm the necessity of improving aesthetic education through the systematic application of national cultural heritage.
Keywords: ethnoculture; aesthetic education; Karakalpak folk culture; oral folk art; national art; spiritual education; pedagogical approach